Pilot Tone Actuated Antenna Array Pattern Reconfiguration - Fusco, Vincent; Zelenchuk, Dmitry E.; Buchanan, Neil B. (IEEE transactions on antennas and propagation, 2014)
A new strategy for remote reconfiguration of an antenna array far field radiation pattern is described. The scheme uses a pilot tone co-transmitted with a carrier signal from a location distant from that of a receive antenna array whose far field pattern is to be reconfigured. By mixing the co-transmitted signals locally at each antenna element in the array an IF signal is formed which defines an equivalent array spacing that can be made variable by tuning the frequency of the pilot tone with respect to the RF carrier. This makes the antenna array factor hence far field spatial characteristic reconfigurable on receive. For a 10 × 1 microstrip patch element array we show that the receive pattern can be made to vary from 35 to 10 degrees half power beam width as the difference frequency between the pilot and the carrier at 2.45 GHz varies between 10 MHz and 500 MHz carrier.